Neonatal Functional and Structural Connectivity Are Associated with Cerebral Palsy at Two Years of Age - Merhar, Stephanie L.; Gozdas, Elveda; Tkach, Jean A.; Parikh, Nehal A.; Kline-Fath, Beth M.; He, Lili; Yuan, Weihong; Altaye, Mekibib; Leach, James L.; Holland, Scott K. (American Journal of Perinatology, 2020)
Objective The accuracy of structural magnetic resonance imaging (MRI) to predict later cerebral palsy (CP) in newborns with perinatal brain injury is variable. Diffusion tensor imaging (DTI) and task-based functional MRI (fMRI) show promise as predictive tools. We hypothesized that infants who later developed CP would have reduced structural and functional connectivity as compared with those without CP.Study Design We performed DTI and fMRI using a passive motor task at 40 to 48 weeks' postmenstrual age in 12 infants with perinatal brain injury. CP was diagnosed at age 2 using a standardized examination.Results Five infants had CP at 2 years of age, and seven did not have CP. Tract-based spatial statistics showed a widespread reduction of fractional anisotropy (FA) in almost all white matter tracts in the CP group. Using the median FA value in the corticospinal tracts as a cutoff, FA was 100% sensitive and 86% specific to predict CP compared with a sensitivity of 60 to 80% and a specificity of 71% for structural MRI. During fMRI, the CP group had reduced functional connectivity from the right supplemental motor area as compared with the non-CP group.Conclusion DTI and fMRI obtained soon after birth are potential biomarkers to predict CP in newborns with perinatal brain injury.
Keywords: functional MRI; diffusion tensor imaging; cerebral palsy; hypoxic–ischemic encephalopathy